IMPLEMENTATION OF INCOME TAX OBLIGATION AND VALUE ADDED TAX ON E -COMMERCE BUSINESS ACTIVITIES - Eben Simanjuntak,; Sartono; Maryano (Scholar Express Journals, 2022)
Rate growth very fast e-commerce cause a number of problem to system collection tax. Transaction e - commerce happening very briefly cause the difficulty for knowing who just actors involved, related transaction location in activity e - commerce transactions that . Then related with characteristics or type products traded and served in digital form (non- physical) so that is one influencing factors the difficulty apply treatment tax to transaction electronics . Due to Internet usage is increasing growing, a lot companies and internet users are concerned that later government will determine broad rules for trading international and e - commerce. Potential fields cause problem in regulation the is Taxes and obligations, prohibitions delivery information , as well as controlling to development standard , giving permission to terms and conditions regulation for providers who provide service .
Keywords: e -commerce; trade international; tax